2017
DOI: 10.1103/physrevb.96.155423
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure and lifetime of dark excitons in transition metal dichalcogenide monolayers

Abstract: The intricate interplay between optically dark and bright excitons governs the light-matter interaction in transition metal dichalcogenide monolayers. We have performed a detailed investigation of the "spin-forbidden" dark excitons in WSe2 monolayers by optical spectroscopy in an out-of-plane magnetic field Bz. In agreement with the theoretical predictions deduced from group theory analysis, magneto-photoluminescence experiments reveal a zero field splitting δ=0.6 ± 0.1 meV between two dark exciton states. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
244
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(273 citation statements)
references
References 60 publications
29
244
0
Order By: Relevance
“…In ref. [], it has been shown that the lifetime of the dark excitons is two orders of magnitude longer than the lifetime of the bright excitons in WSe 2 . We see a similar trend in our experimental results compared to previously measured lifetimes of defect‐localized states in WSe 2 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In ref. [], it has been shown that the lifetime of the dark excitons is two orders of magnitude longer than the lifetime of the bright excitons in WSe 2 . We see a similar trend in our experimental results compared to previously measured lifetimes of defect‐localized states in WSe 2 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The emergent valley-contrasting properties not only impact quasiparticles, but also are expected to give rise to new physics involving zone edge phonons, or valley phonons, which are collective lattice oscillations at the corners of hexagonal Brillouin zone (±K points). These phonons have been predicted to play an important role in spin and valley pseudospin relaxation through phononassisted intervalley scattering 7,8 . Additionally, valley phonons can possess chirality with intrinsic pseudo-angular momentum 9 , which has recently attracted wide attention [10][11][12][13] .…”
Section: Maintextmentioning
confidence: 99%
“…Here, we identify the signatures of multiple valley phonons in monolayer WSe2. The monolayer WSe2 hosts stable and long-lived dark exciton and trion as ground states [17][18][19][20][21][22] . The resulting accumulated exciton and trion populations are highly desirable for studying their interactions with phonons.…”
Section: Maintextmentioning
confidence: 99%
“…Notably large g-factors (about-8) have been recently reported for intra valley dark excitons in WSe 2 monolayer encapsulated in hBN [56]. Our simple consideration takes into account recombination of neutral complexes.…”
Section: Experimental Data/assumptionsmentioning
confidence: 99%